A retrospective, descriptive study of hepatitis C testing, prevalence, and care continuum among adults on probation - Kevin F. Kamis; David L. Wyles; Matthew S. Minturn; Tracy Scott; Dean McEwen; Hermione Hurley; Scott J. Prendergast; Jessie Gunter; Sarah E. Rowan (BMC, 2022)
Abstract Background Despite constituting the largest segment of the correctional population, individuals on court-ordered probation remain largely unstudied with respect to hepatitis C virus (HCV) testing and linkage-to-care. We conducted a retrospective, descriptive analysis to estimate prevalence of diagnosed HCV and the subsequent HCV care cascade among a cohort of individuals enrolled in an adult probation program over a 25-month period in Denver, Colorado. Methods We utilized probabilistic matching with first and last name, sex, and birthdate to identify individuals enrolled in probation between July 1, 2016 and July 30, 2018 who had a medical record at the participating safety-net healthcare institution as of December 31, 2019. Electronic medical record data were queried for evidence of HCV testing and care through June 30, 2021. The state HCV registry was also queried for prevalence of reported HCV cases among the cohort. Results This cohort included 8,903 individuals; 6,920 (78%) individuals had a medical record at the participating institution, and of these, 1,037 (15%) had ever been tested for HCV (Ab or RNA) and 308 (4% of those with a medical record, 30% of those tested) had detectable HCV RNA. Of these, 105 (34%) initiated HCV treatment, 89 (29%) had a subsequent undetectable HCV viral load, and 65 (21%) had documentation of HCV cure. Eleven percent of the total cohort had records of positive HCV Ab or RNA tests in the state HCV registry. Conclusions This study demonstrates the importance of HCV screening and linkage-to-care for individuals enrolled in probation programs. A focus on this population could enhance progress towards HCV elimination goals.